The cost-effectiveness of different diagnostic options of TB among HIV-infected patients - V. E. Shumlyanskaya; A. V. Rudakova (Журнал инфектологии, 2014)
Diagnostic of active tuberculosis among HIV – infected people is difficult problem, demanding of significant healthcare costs.The objective: to evaluate the cost-effectiveness of different diagnostic scenarios detecting tuberculosis among HIVinfected.Material and methods: the evaluation was carried out through modeling, from the health care system perspective, in cohorts with different CD 4+ counts (<200, 200–499, >500). The three scenarios were examined: (1) «Base» – the current TB diagnostic scheme in the Russia; (2) «Addition» – the «Base» scenario augmented by Xpert/Rif; (3) «Replacement » – only one Gene Xpert/Rif.Results: using «Addition» scenario in CD 4+cohort <200, allows to detect 8 additional TB patients per 1000 HIV-infected people, significantly increases the number of effectively treated patients, including patients with initial rifampicin drug resistant, prevents 5 deaths, reduce opportunity oftransmission TB and further spread TB in population. Additional costs per one additional effectively treated patient, identified in the «Addition» scenario, compared to «Basic», is 1130 thousand rubles, additional costs per one prevented death is 943 thousand rubles. Using the algorithm «Replacement » can lead to significant diagnostic delays, its use hasneither clinical nor economic feasibility.Conclusions: adding Gene Xpert MBT/Rif to the TB diagnosticalgorithm is economically feasible in patient cohort with CD 4+ <200 cells/ml.